Ultrasound Simulation for Training Trainees when the Luxury Becomes Essential: Opinion and Evidence Obtained during the Latvian Research Council Project Implementation - Vedmedovska, Natālija; Ķīvīte-Urtāne, Anda; Lisovaja, Ija; Rācene, Laura; Ķīse, Līva; Sārta, Beāte; Vaska, Agnija; Rostoka, Zane; Bule, Violeta; Pitkēviča, Ieva; Rezeberga, Dace (Acta medica Lituanica, 2022)
Background. Simulation as a proxy tool for conditional clinical training became a powerful technique for introducing trainees to the ultrasound imaging world, allowing them to become a trained sonographer taking into consideration different rates of progress completing a specific task against the time and ensuring the long-lasting maintenance of the obtaining practical skills. Adding a costly, but effective high-fidelity simulator to the residency program justified the expense, demonstrating efficiency of training for improving the clinical performance and confidence of trainees. Materials and methods. A pilot study in Riga Maternity Hospital within the framework of the study “Role of metabolome, biomarkers and ultrasound parameters in successful labour induction” (Fundamental and Applied Research Programme lzp-2021/1-0300) was performed between March 1st 2022 and 31st April 2022. A virtual-reality simulator (Scantrainer, MedaphorTM, Cardiff, UK) was used with the teaching module for assessment of the uterine cervix. Five trainees in obstetrics and two young specialists included in the study. None of them had Fetal Medicine Foundation certificate of competence in the assessment of the uterine cervical lenght before. The time used on the simulator, the number of simulations and a mean confidence in cervical length assessment before and after simulation were recorded. Results. The study on assesment of uterine cervical lenght demonstrated statistically significant increase in confidence (p=0.008) and statistically significant decrease in time needed to complete correctly the same tasks for the trainees (p=0.008) that shows a positive learning curve over the time of training on ScanTrainer, Medaphor. Conclusions. The simple task allows to become a certified specialist in uterine cervical assessment in the short period of time. That support the productiveness of the simulation-based education. The training program should be updated taking into consideration simulation curriculum.